Intermediate Microeconomics with Microsoft Excel - Barreto, Humberto (Open textbook library., 2020)
This book is based on the idea that there is a particular framework used by economists to interpret observed reality. This framework has been called the economic way of thinking, the economic approach, and the method of economics. This book is different from the many other books that attempt to teach microeconomics in three ways: It explicitly applies the recipe of the economic approach in every example. It uses concrete examples via Microsoft Excel in every application, which enables the reader to manipulate live graphs and learn numerical methods of optimization. The majority of the content is in the Excel workbooks which the reader uses to create meaning. You learn by doing, not by reading.